LOS ANTHIDIINI DE CHILE: CLAVE PARA ESPECIES (HIMENOPTERA: MEGACHILIDAE) - Toro, Haroldo; Rodríguez, Sharon (Acta Entomológica Chilena, 2022)
The chilean species of Anthidiini are considered in this paper; the following species are keyed out: Notanthidium steloides (Spinola), Allanthidium (Allanthidium) bidentatum (Friese), Allanthidium (Allanthidium) rodolfi (Ruiz), Allanthidium (Anthidianum) bizonatum (Friese) Anthidium adriani Ruiz, Anthidium aymara n.sp., Anthidium chítense Spinola, Anthidium chubuti Cockerell, Anthidium colliguayanum Toro y Rojas, Anthidium decaspilum Moure, Anthidium deceptum Smith, Anthidium edwini Ruiz, Anthidium espinosai Ruiz, Anthidium falsificum Moure, Anthidium funereum Schletterer, Anthidium gayi Spinola, Anthidium kuscheli Moure, Anthidium penai Moure, Anthidium peruvianum Schrottky. The following ñames are considered synonyms: A. anurospilum Moure n. sin. for A. espinosai Ruiz; A. gutierrezi Moure n. sin. for A. chubuti Cock. A new species, Anthidum aymara n. sp., from the north of Chile is described.